Promotion of oxidative stress is associated with mitochondrial dysfunction and muscle atrophy in aging mice. Issue 1 (22nd November 2019) - Kadoguchi, Tomoyasu; Shimada, Kazunori; Miyazaki, Tetsuro; Kitamura, Kenichi; Kunimoto, Mitsuhiro; Aikawa, Tatsuro; Sugita, Yurina; Ouchi, Shohei; Shiozawa, Tomoyuki; Yokoyama‐Nishitani, Miho; Fukao, Kosuke; Miyosawa, Katsutoshi; et al.
Abstract : Aim: We examined the changes in oxidative stress, mitochondrial function and muscle atrophy during aging in mice. Methods: We used 6‐, 12‐ and 24‐month (6 M, 12 M and 24 M)‐old C57BL/6J mice. Skeletal muscles were removed from the lower limb and used for quantitative real‐time polymerase chain reaction, immunoblotting and histological analyses. Results: The muscle weight and myocyte cross‐sectional area were significantly decreased in the 12 M and 24 M mice compared with those of the 6 M mice. The levels of the oxidative stress markers, nicotinamide adenine dinucleotide phosphate oxidase 2, nicotinamide adenine dinucleotide phosphate oxidase 4, mitochondrial 4‐hydroxy‐2‐nonenal and 3‐nitrotyrosine, were significantly higher in the 24 M mice compared with those of the 6 M mice. Furthermore, the 24 M mice had lower levels of mitochondrial markers, peroxisome proliferator‐activated receptor gamma coactivator 1 (PGC)‐α, peroxisome proliferator‐activated receptor gamma coactivator‐1β, sirtuin‐1, adenosine triphosphate synthase mitochondria F1 complex α subunit 1 and mitochondrial cytochrome c oxidase 1. The ubiquitin–proteasome pathway genes muscle ring finger‐1 and atrogin‐1 were significantly upregulated in the 12 M and 24 M mice, and protein synthesis markers (phosphorylated‐Akt and ‐p70 ribosomal S6 kinase) were significantly lower in the 24 M mice compared with the 6 M mice (all P < 0.05). Conclusions: These findings have important implications for the mechanisms that underlie sarcopenia and frailty processes. Geriatr Gerontol Int 2020; 20: 78–84 .